Research Development Of Tiktok Video Media About Anemia Prevention In Adolescent Girls At SMP Negeri 18 Surakarta - Handayani, Lidya Putri; Afriyanto, Dzul Fahmi; Prasetyo, Budi (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Anemia is one of the health problems that occur in adolescents. According to Basic Health Research in 2018, in Indonesia the prevalence of anemia in adolescents is 32%, which means that 3-4 out of 10 adolescents suffer from anemia. The purpose of this research is to develop health media through Tiktok videos about the prevention of anemia in adolescent girls at SMP Negeri 18 Surakarta. This study uses the Research and Development (R&D) method of the Borg & Gall development model with data collection, research planning, product design, design validation, design revision, product testing and product revision. The subject of the small-scale research was 10 students as a sample and field trials were carried out with 30 students. The results of this study show that the average score of the material expert validation test is 90% with the very feasible category and the validation of media experts is 90% with the very feasible category. The feasibility test of the product with student validation of 91% with the category of very feasible. The conclusion of the research and development of Tiktok video-based audio-visual media is very feasible to be used in the educational process of preventing anemia in adolescent girls.